Graphene Oxide: Realizing Ultralow Concentration Gelation of Graphene Oxide with Artificial Interfaces (Adv. Mater. 8/2019). Issue 8 (19th February 2019) - Luo, Chong; Lv, Wei; Qi, Changsheng; Zhong, Lixiang; Pan, Zheng‐Ze; Li, Jia; Kang, Feiyu; Yang, Quan‐Hong
Abstract : A cocktail preparation is employed by Wei Lv, Jia Li, Quan‐Hong Yang, and co‐workers in article number1805075 to demonstrate the ultralow‐concentration gelation of graphene oxide (GO) in a water–isopropyl‐alcohol mixture, where the two different colored liquids represent water and isopropyl alcohol respectively. Microphase separation takes place, due to the different intercalation energies of the GO in the two liquids, generating artificial liquid–liquid interfaces that facilitate interactions between the sheets and the formation of a three‐dimensional graphene network.